COMPLETE AND INCOMPLETE BONY BRIDGES NEAR FORAMEN OVALE WITH POTENTIAL SURGICAL AND CLINICAL IMPLICATIONS - MEHTA, RITUBHI; SHARMA, JAGMOHAN; SINGH, PANKAJ KUMAR; CHHABRA, PRABHJOT KAUR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Pterygospinous or Pterygoalar ligaments may pose mandibular nerve compression by when present near foramen ovale. The presence of ossified pterygospinous or pterygoalar ligaments might cause trouble to surgeons in performing percutaneous rhizotomy for trigeminal neuralgia, electroencephalographic procedures, or taking biopsy from cavernous sinus tumors. The present study aims to find the incidence and specific morphological variations related to the ossification of pterygospinous and pterygoalar ligaments. Methods: The study was conducted on 200 dried adult human cadaveric skull of unknown age and sex in the department of Anatomy, Mahatma Gandhi Medical College and Hospital, Jaipur. Skulls were obtained from different medical colleges of the Rajasthan region. The study included fully dried, intact, adult human skull bones with no structural defects. Damaged, fractured, skull with the developmental anomaly, injured or pathologically malformed skull especially at or near the foramen ovale on either side were excluded from the study. Ossification of pterygospinous and pterygoalar bar was studied on both sides. Statistical analyses were performed using SPSS Version 26 software. Results: Ossified ligaments were studied in 400 sides of 200 skulls. The ossification of pterygospinous bar was observed in 53 cases (13.25%). The pterygospinous bar was complete in twelve (3%) cases and incomplete in 41 cases (10.25%). The ossified pterygoalar ligament was observed in 62 cases (15.5%). Ossification was complete in 15 cases (3.75%) and incomplete in 47 cases (11.75%). Conclusion: Ossification of pterygospinous and pterygoalar bars was observed in skulls obtained from medical colleges in the Rajasthan region. Knowledge of such morphological variations of the skull base will improve the therapeutic outcomes in the treatment of trigeminal neuralgia.